Answer: [tex]\frac{3}{2}x+y=-\frac{17}{2}[/tex]
Step-by-step explanation:
The standard form of a linear equation is [tex]ax+by=c[/tex]
So we need to solve for c
Start by simplifying everything in the equation
[tex]y+7=-\frac{3}{2} (x+1)[/tex]
Use the Distributive Property
[tex]y+7=-\frac{3}{2}x-\frac{3}{2}[/tex]
Now subtract 7 from both sides
[tex]y+7=-\frac{3}{2}x-\frac{3}{2}\\y+7-7=-\frac{3}{2}x-\frac{3}{2}-7\\y=-\frac{3}{2}x-\frac{17}{2}[/tex]
Add [tex]\frac{3}{2} x[/tex] to both sides
[tex]y+\frac{3}{2}x=-\frac{3}{2}x+\frac{3}{2}x-\frac{17}{2}\\\frac{3}{2}x+y=-\frac{17}{2}[/tex]
NOTE: [tex]-\frac{17}{2}[/tex] simplifies to -8.5 if you find that more desirable